Propagation models and measurements for microcellular communication systems - Tan, Soon Yim. (2009)
This thesis contains the formulation of theoretical models and the results of experimental studies for the problem of microwave propagation and scattering in microcellular communications systems for urban areas and for indoor scenes. In an urban environment, a quasi-three-dimensional vector propagation model based on the uniform theory of diffraction (UTD) has been developed, using multiple-image theory and a ray launching technique to describe the multiple reflections and diffractions. The model is applicable to a general street scene with various distributions of streets, buildings with complex geometries such as empty squares, re-entrant building geometries, angled streets with wedge-shaped corners at the junctions, rounded building corners, open areas etc.